Teacher Recruitment Management at Al-Azhar Arabic Language Course Pare Kediri - Fikri, Maulana Ahsanul (Nurul Jadid University, 2023)
One of the reasons for the success of education is that it has good management that manages this process. One of the educational institutions that has become famous for successfully teaching the Arabic language is the Al-Azhar Course for Teaching the Arabic Language located in Bari Kediri. Therefore, the researchers wanted through this research to describe the management of teacher recruitment in the Al-Azhar Course because of the teachers who are proficient in their fields. This research uses the qualitative approach. Data collection is done through observation, interview and documentation. The results of this research indicate that this institution has been well managed in teacher recruitment. This is done through four steps in total, which are: 1) Preparation; by preparing all the equipment for recruitment. 2) Implementation; by testing registrants from different types of tests. 3) Recruitment; by appointing accepted registrants as teachers according to the required admission requirements such as the educational course. 4) Evaluation, by observing the principal or others towards the education of the new teacher. After the teacher has been hired, the course takes care of the teacher; by specifying the provision of teacher care and professional development so that teachers are always motivated to improve their abilities in an academic and non-academic field. By managing recruitment on these patterns, qualified teachers are produced to teach Arabic using high quality human resources in Al-Azhar Bari Kediri Course.